Pancreatectomy is underused in NSW regions with low institutional surgical volumes: a population data linkage study. Issue 1 (16th January 2017) - Creighton, Nicola; Walton, Richard; Roder, David M; Aranda, Sanchia; Richardson, Arthur J; Merrett, Neil; Currow, David
Abstract: Objective: To examine differences in the proportions of people diagnosed with pancreatic cancer who underwent pancreatectomy, post‐operative outcomes and 5‐year survival in different New South Wales administrative health regions of residence. Design, setting and participants: Retrospective analysis of NSW data on pancreatic cancer incidence and surgery, 2005–2013. Main outcome measures: The proportion of newly diagnosed patients with pancreatic cancer who were resected in each region; 90‐day post‐operative mortality; one‐year post‐operative survival; 5‐year post‐diagnosis survival. Results: 14% of people diagnosed with pancreatic cancer during 2010–2013 (431 of 3064) underwent pancreatectomy, an average of 108 resections per year. After adjusting for age, sex and comorbidities, the proportion that underwent resection varied significantly between regions, ranging between 8% and 21% ( P <0.001). Higher resection rates were not associated with higher post‐operative 90‐day mortality or lower one‐year survival (unadjusted and risk‐adjusted analyses). Higher resection rates were associated with higher 5‐year post‐diagnosis survival: the mean survival in regions with resection rates below 10% was 3.4%, compared with 7.2% in regions with rates greater than 15% (unadjusted and adjusted survival analyses; P <0.001). There was a positive association between regional resection rate and the pancreatectomy volume of hospitals during 2005–2009. An additional 32 people would be resected annually if resection rates in low rate regions were increased to the 80th percentile regional resection rate (18%). Conclusion: There is significant geographic variation in the proportion of people with pancreatic cancer undergoing pancreatectomy, and the 5‐year survival rate is higher in regions where this proportion is higher.